Dataset of annual metal scrap circularity of titanium industry in China from 2005 to 2020 - Wenhao Wang; Fuzhong Wu (Scientific Data, 2023)
Abstract Titanium products, regarded as a strategic metal by many national governments, play important and irreplaceable roles in national defence and military applications. China has built a large-scale titanium industrial chain, and its status and development pathways will greatly affect the global market. Several researchers contributed a set of reliable statistical data to bridge the knowledge gap in evaluating the industrial layout and the entire structure of China’s titanium industry with little literature information regarding the management of metal scrap in the manufacturers of titanium products. To bridge this data gap, we present a dataset of annual metal scrap circularity to uncover China’s evolution of the titanium industry today, which contains off-grade titanium sponge, low-grade titanium scrap, and recycled high-grade titanium swarf with the relevant circularity of the titanium industry in China at the national level from 2005 to 2020.